PENGARUH KOMPLEKSITAS OPERASI, PERGANTIAN AUDITOR DAN INVESTMENT OPPORTUNITIES TERHADAP AUDIT REPORT LAG (Studi Empris pada Perusahaan Pertambangan dan Pertanian yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Indri, Putri Silvia; Andreas, Andreas; Volta, Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine and analyze the effect of operational complexity, auditor turnover and investment opportunities on the audit report lag. Operation complexity is measured using a dummy. Auditor turnover in this study was measured using a dummy. And investment opportunities in this study are measured using the market to book value of equity (MVE / BE) ratio. The population in this study were mining and agricultural companies listed on the Indonesia Stock Exchange in 2016-2018. The sample of this study was selected with purposive sampling criteria so that 11 mining companies and 15 agricultural companies were selected that met the criteria. Hypothesis testing is done using multiple regression methods which are then analyzed using SPSS version 18.00 for Windows. The results of this study indicate that the complexity of operations has a significant effect on audit report lag in mining and agricultural companies on the Indonesia Stock Exchange. Meanwhile, the change of auditors and investment opportunities did not affect the audit report lag for mining and agricultural companies on the Indonesia Stock Exchange.Keywords: Operation Complexity, Auditor Change, Investment Opportunities, Audit Report Lag